Analyzing Errors in Students’ Writing - Aristia, Erni Sona; Ismiati, Ismiati (Universitas Muhammadiyah Mataram, 2023)
The purpose of this study was to examine the mistakes that eighth-grade Madrasah Tsanawiyah (MTS) students made when composing recount texts. There were 27 pupils enrolled. The research method used is qualitative design. Interviews, paperwork, and tests were used to gather data, which was then identified, categorized, and explained (calculated), and errors were assessed. The results demonstrate that pupils made mistakes in addition, subtraction, miss-formation, and ordering. There were 264 mistakes in total. There were 23% omission errors, 13% addition errors, 57% miss-formation errors, and 7% miss-ordering errors. There were 68 errors in omission, which may be divided into 8 prepositional, 10 article, 28 to be, 17 subject, and 5 noun omissions. When crafting a sentence, the students failed to include grammatical morphemes, certain necessary components of proper sentences, and the items that belong in the phrase. The 28 addition errors were divided into 3 noun addition errors, 2 preposition addition errors, 12 article addition errors, 1 conjunction addition error, 9 to be addition errors, and 1 auxiliary addition error. 140 miss-formation mistakes, divided into 14 categories. 20 misspelled words, 16 misspelled plural words, fifteen word choice/word form, eight possessive form, five auxiliary, twenty-three present verb for third-person singular, six subjects, nine, preposition, ten verbs, twenty pronouns, and thirty-two misspelled articles. Incorrect morpheme placement was frequently cited as the cause of the students' sentences' incorrect order. In this investigation, 23 miss-ordering problems were discovered.